Um estudo de aplicação das teorias da expectativa e da ancoragem na motivação para o desempemho de alunos do ensino médio - Hintemann, Luiz Henrique (2006)
This thesis presents a study on Tversky & Kahneman s (1974) Anchoring theory, and Vroom s (1964) Expectance theory in the context of education and students motivation. It is surveyed 424 students of a secondary and agricultural technical school in Brazil Northeast (EAJ). The survey form try to capture the Vroom s Expectance Theory constructs of Valence, Instrumentality, Expectation and Motivational Force, and also the Tversky and Kahneman Anchoring effect in terms of grade expected. The main findings suggest that the minimum grade required by the school is much strong in driving the students motivation and performance than the Expectancy Theory. It was found that the different grades required drive the students to pursue different grade in the same way